Analisis Pengaruh Return On Equity, Debt to Equity Ratio dan Pertumbuhan Penjualan (Growth) Terhadap Harga Saham Perusahaan Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2021 - Sholi Robiyatun; Deni Ramdani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The COVID-19 pandemic has resulted in a shift in human lifestyles and increased sensitivity to health. The demand for health products is increasing in response to several policies from the government. The purpose of this study is to determine the effect of the Return on Equity Ratio, Debt to Equity Ratio, and Sales Growth (Growth) on the Stock Prices of Pharmaceutical Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period. The sample used is all pharmaceutical companies listed on the Indonesia Stock Exchange, then the selection is made using the purposive sampling method. The data analysis technique used is multiple linear analysis using SPSS 25 software. The partial results show that the Return on Equity variable has a positive and significant effect on stock prices. While the other two independent variables, namely Debt to Equity Ratio and growth did not affect stock prices. However, the test results simultaneously show that all independent variables, namely Return on Equity, Debt to Equity Ratio, and Sales growth (Growth) jointly affect the company's stock price.